Discursive construction of neighborhood across Brooklyn: a corpus-ethnographic approach - dorpus data - Berberich, Kristin (Universität, 2021)
This data set consists of several sub-corpora used for the analysis of the discursive construction of 'neighborhood' in Brooklyn, New York. It comp...